A batch study of hexavalent chromium removal from synthetic wastewater using modified Russian knapweed flower powder - Mohammad Taghi Ghaneian; Mahboobeh Dehvari; Behzad Jamshidi (International Journal of Environmental Health Engineering, 2014)
Aims: In this research, modified Acroptilon repens (Russian knapweed) flower powder was used as a novel adsorbent for removal of Cr (VI) from synthetic wastewater. Materials and Methods: The batch adsorption studies were performed under various laboratory conditions with initial chromium concentrations of 2, 10 and 15 mg/l, adsorbent dose of 0.05-0.2 g/100 ml, contact time of 30-240, min and pH of 2-9. The solution was mixed with a mechanical shaker with 120 r.p.m. at 20°C. The suitability of the adsorbent was evaluated using Langmuir, Freundlich and Temkin isotherm models. For kinetic study, pseudo-first-order and pseudo-second-order kinetics were used. Results: The results indicated that maximum adsorption was achieved in acidic conditions. The optimum pH for the removal was 2. The capacity of chromium adsorption at equilibrium conditions increased by increasing the concentration of the adsorbate. The results also showed that the removal efficiency of Cr (VI) increased with increasing contact time. On increasing the initial concentration of the Cr (VI) solution, chromium removal reduced. The Freundlich and Langmuir isotherm models gave better accordance to the adsorption data in comparison with the Temkin equation. Adsorption of Cr (VI) followed pseudo-second-order kinetics rather than the pseudo-first-order kinetics. Conclusion: This study showed that modified Russian knapweed flower powder can be used as an effective lignocellulosic biomaterial and biosorbent for removal of Cr (VI) from wastewater.